2006
DOI: 10.1111/j.1526-4610.2006.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Migraine Prevention With Topiramate: Open‐Label Extension of Pivotal Trials

Abstract: Patients receiving topiramate experienced a sustained reduction in migraine frequency for up to 14 months. The effectiveness and safety of topiramate was consistent with that observed during 2 26-week pivotal trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 17 publications
2
59
0
Order By: Relevance
“…In this extension phase, patients had a sustained reduction in mean monthly migraine frequency, regardless of the type or dose of study medication received in the double-blind phase (topiramate or placebo). The safety of topiramate was consistent with that observed during the two 26-week pivotal trials [43].…”
Section: Pharmacokineticssupporting
confidence: 81%
See 1 more Smart Citation
“…In this extension phase, patients had a sustained reduction in mean monthly migraine frequency, regardless of the type or dose of study medication received in the double-blind phase (topiramate or placebo). The safety of topiramate was consistent with that observed during the two 26-week pivotal trials [43].…”
Section: Pharmacokineticssupporting
confidence: 81%
“…To have a substantial effect on the evolution of migraine, benefits of prophylaxis should persist even after its withdrawal [43]. When treatment is discontinued, the frequency of migraine increases instead already in the first 4 weeks after discontinuation [67].…”
Section: Expert Opinionmentioning
confidence: 99%
“…A big Open-Label Extension of Pivotal Trials, in which 403 patients completed the trial, also included patients aged 12-18 years [Rapoport et al, 2006]. These authors concluded that patients receiving topiramate experienced a sustained reduction in migraine frequency for up to 14 months (5.572.3 attacks/month at baseline versus 3.472.6 attacks/ month at the end of the 6-month double-blind phase and 2.272.4 attacks/month after an additional 8 months of open-label topiramate).…”
Section: Topiramatementioning
confidence: 99%
“…The minimum suggested trial to assess the benefits of prophylaxis is in fact 2-3 months [6,7,11], although many physicians prefer longer treatment periods, which can give more relevant results, as indicated by recently published trials [13,14]. After such a treatment period, the same or a different compound can be prescribed for a similar or for longer periods, taking into account the efficacy and tolerability of the first prescription as assessed at follow-up visits.…”
Section: Introductionmentioning
confidence: 99%